Evaluation Multi Diabetes Mellitus Symptoms by Integrated Fuzzy-based MCDM Approach - et. al., Qahtan M.Yas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, diabetes is one of the most dangerous diseases spreading among people around the world. The most prominent reasons for the spread of this type of the disease are social, behavioral and medical factors. Different types of diabetes mellitus affecting both men and women were discussed by researchers. Various symptoms caused to the disease was determined by physicians. These symptoms were classified as criteria in this study according to the literature. The paper aims to evaluation preferences of the diabetes symptoms for patients by adapting decision-making techniques. Multiple criteria decision-making techniques were used to solve the decision-making problems in this study. The study methodology consists of three stags; 1) Determine multi criteria of diabetes mellitus symptoms according to the literature; 2) Calculation of parameter weights using triangular fuzzy numbers approach; 3) Selection the best and worst alternative of diabetes patients by applying the fuzzy- technique of order preference similarity to the ideal solution (TOPSIS) method according to the multiple symptoms. Results were obtained from selecting the best patient at (P248), while the worst patient was identified at (P333). Hence, this study may assist patients and doctors in taking appropriate measures aimed at reducing the incidence of diabetes.